Entrepreneurial education in the school curriculum: in search of positioning in Zimbabwe - Gwendoline V. Nani (Problems and Perspectives in Management, 2016)
This study was conducted to find out when Entrepreneurship can be introduced in the school curriculum. A case study design premised in the qualitative approach was employed, which used semi-structured focus group interviews as data collection instruments. The areas of study were purposively selected government primary and secondary schools in the Bulawayo Metropolitan Province in Zimbabwe. Data were analyzed thematically and discussed according to research objectives. Findings revealed that Entrepreneurship per se is not taught in government primary and secondary schools. Based on these findings, the recommendations were that Entrepreneurship should be introduced in the school curriculum at primary level to allow learners to lay a solid foundation for creativity, nurturing and innovation of business ideas for use later in life